Comparison of Carotid Atherosclerotic Plaque Characteristics by High-Resolution Black-Blood MR Imaging between Patients with First-Time and Recurrent Acute Ischemic Stroke - Liu, X.S.; Zhao, H.L.; Cao, Y.; Lu, Q.; Xu, J.R. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: It has been shown that patients with a first ischemic stroke are at high risk of developing recurrent stroke due to carotid atherosclerotic plaque rupture. However, no one has defined the difference in plaques between initial and recurrent stroke. This study sought to investigate the characteristics of carotid plaque between patients with first-time and recurrent acute ischemic stroke by using MR imaging. MATERIALS AND METHODS: Eighty-nine patients with recent acute ischemic stroke were recruited. All subjects underwent carotid high-resolution black-blood MR imaging. The index carotid arteries, defined as the arteries responsible for the ipsilateral stroke, were analyzed quantitatively and qualitatively. Carotid plaque burden and compositional features between patients with first-time and recurrent ischemic stroke were compared. RESULTS: Of 89 recruited patients, 51 had first-time stroke and 38 had recurrent stroke. The mean WA, WT, and PWV were greater in patients with recurrent stroke than in patients with first-time stroke (all, P < .05). Compared with patients with first-time stroke, those with recurrent stroke showed significantly higher prevalence of calcification (44.7% versus 23.5%, P = .035) as well as a larger volume of LRNC (179.14 ± 254.81 mm2 versus 71.65 ± 111.15 mm2, P = .027). IPH or fibrous cap rupture or both were observed in 15.8% of patients with recurrent stroke and 3.9% of patients with first-time stroke. CONCLUSIONS: Carotid plaques in patients with recurrent ischemic stroke are significantly aggravated compared with those in patients with first-time stroke, and monitoring carotid plaques in patients with initial stroke by MR imaging may be helpful for secondary stroke prevention. IPHintraplaque hemorrhageLAlumen areaLRNClipid-rich necrotic coreMPRAGEmagnetization-prepared rapid acquisition of gradient echoPWVpercentage wall volumeTOFtime-of-flightTVAtotal vessel areaWAwall areaWTwall thickness